MODEL PEMBELAJARAN KOOPERATIF TEAMS GAMES TOURNAMENT SEBAGAI UPAYA MENINGKATKAN KEMAMPUAN KOLABORASI DAN HASIL BELAJAR IPA PADA SISWA KELAS V SD GUGUS VI ABIANSEMAL - Artini, Ni Nyoman; Jampel, I Nyoman; Suma, Ketut (Jurnal Administrasi Pendidikan Indonesia, 2025)
Conventional learning models that are often used in elementary schools tend to be teacher-centric and provide less opportunities for students to collaborate and learn actively. This results in low collaboration skills and student learning outcomes, especially in science subjects. This study aims to test the effectiveness of the Teams Games Tournament (TGT) learning model in improving students' collaboration skills and science learning outcomes. The subject of this study is grade V students of SD Group VI, Abiansemal District, which consists of an experimental group taught using the TGT model and a control group taught using a conventional learning model. The research method used is a quasi-experiment with a non-equivalent control group design, involving quantitative data analysis through normality, homogeneity, ANOVA, and MANOVA tests to test hypotheses. The results showed that there was a significant difference in collaboration skills and science learning outcomes between the group of students taught with the TGT model and the group of students taught with the conventional model. The average score of collaboration ability and science learning outcomes of students in the TGT group is in the very high category, while the conventional group is in the high category. The TGT model has been proven to be able to create a learning environment that supports social interaction, increases student motivation, and provides a fun and meaningful learning experience. The implications of this study show that the TGT model can be used as an effective learning alternative to improve the quality of education, especially in developing 21st century skills such as collaboration and critical thinking, so it is recommended to be widely implemented in elementary schools and further developed at different levels of education.